Investigation of testosterone and estrogen plasma concentrations and its relationship in anestrus mares in Kelantan - Ahmad Hanif M Amin (2021)
The plasma testosterone and estrogen concentrations and relationship with estrus behaviour were investigated in anestrus (n=15) and normal estrus mares (n=5). Anestrus mares were categorised into age groups (6-9, 10-13 and 14-17 years), breed (Arab, Thoroughbred and Polo) and body weight (300-350kg, >350-400kg, >400-450kg). Alternate day blood sampling was done on all mares where blood was sampled for 14 times from each mares. Before blood samples were taken, all mares were teased, and their estrus behaviour were observed and recorded. All mares were teased with stall teasing method, with stallions kept inside the stall and the mares were held outside the stall. The estrus cycle of all mares were assigned to day 13 according to maximum estrogen plasma concentrations. Daily average, mean maximum and mean periovulatory plasma testosterone and estrogen concentrations were found to be significantly higher (p<0.05) in control compared to anestrus mares. The plasma testosterone and estrogen periovulatory concentrations were significantly higher (p<0.05) in control mares compared to anestrus mares in all categories (age, breed and body weight). There were no significant difference of mean testosterone and estrogen periovulatory concentrations between anestrus mares of different ages and breeds except body weight (p<0.05) where a significant increased (p<0.05) in testosterone were noticed from day 9 to day 11 in control mares compared to anestrus mares. Anestrus and control mares showed decreased of testosterone concentrations on day 13 until day 17. Estrogen concentrations exceeded testosterone concentrations from day 13 to day 17 (5 days) in control mares. More intense estrus behaviour were observed on control mares in comparison to anestrus mares. Estrogen has stonger correlation (p<0.05) with estrus behaviour compared to testosterone. The ovarian status has no effect in estrus score in anestrus mares (p>0.05) since anestrus mares with active and inactive ovaries showed the same estrus score. A clear relationship of estrus score were presented in control mares under the influence of estrogen during periovulatory period (p<0.05) compared to testosterone. The anestrus mares also showed an elevated estrus score from 0 to 1 during the period when estrogen were dominating and with concomitant increased in estrus score during periovulatory period. The testosterone effect during periovulatory and postovulatory were crucial as to prime estrogen production adequate for estrus behavior response but negatively interfered with FSH secretions in mares respectively. The evidence of short rise of estrogen plasma concentrations might indicate termination effect by a concomitantly higher testosterone to estrogen concentrations in anestrus mares. In addition, the association of estrus behaviour in mares were stronger with estrogen. The reduced in estrus scores after the maximum estrogen concentrations which were noticed on day 13 to day 15 in control mares (from 3.8 to 1 estrus score) was a good indicator that ovulation has taken place 2 days prior to an end of estrus in mares. The estrogen were primed by testosterone during periovulatory period however, with the constant domination of testosterone over estrogen, this condition eventually interfered with FSH secretions in anestrus mares. Estrogen insufficiencies were the result of FSH suppression by the testosterone that interfered with follicle formations and poor follicular estrogenic secretions in anestrus mares. The study has proven that the anestrus were closely related to abnormal reproductive physiology that was characterized by imbalanced testosterone and estrogen concentrations in mares. This information could be applied to strategic breeding management and optimizing anestrus mares for an impactful economic return to horse breeders in Malaysia and could be applicable to other tropical regions.